The Development and Evaluation of The Instructional Kid Blog for Teaching Selected Computer Science Concepts in Primary Schools in Ilorin Metropolis - Daramola, Florence Olutunu (Indonesian Journal of Teaching in Science, 2022)
This study determined the development and evaluation of an instructional kid blog for teaching selected computer science concepts in primary schools in the Ilorin metropolis. The study adopted design-based research to ten experts from both the educational technology and computer sciences department at the University of Ilorin and five computer studies teachers in Ilorin. The findings indicate that the instructional kid blog was well structured and every expectation was achieved. Both experts and teachers have positive reactions and developed an instructional kid blog that satisfied the required expectations. The study concluded that the instructional kid blog is a powerful instructional tool in the classroom that the ability to enhance teaching and learning in Nigeria. Therefore, it was recommended that an instructional kid blog should be adopted for teaching computer science in primary school in Ilorin to concretize lesson content and abstract that is inherent in computer science.